A porous film material and a preparation method thereof
Hydrophilic polymers and functionalized nanodiamond porous film materials prepared through electrospinning technology solve the problem of insufficient mechanical properties and wettability of lithium battery separators, achieve efficient improvement of lithium battery separators, and extend the lithium battery separators Service life and battery life.
Patent Information
- Application Number
- CN202211737958.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The existing lithium battery separators have shortcomings in mechanical properties, wetting properties and porosity, resulting in limited service life and battery life of lithium batteries, and the binding force of existing modification methods is weak and unstable.
Electrospinning technology is used to prepare porous film materials, using hydrophilic polymers and functionalized nanodiamonds as main components, and the binding force between nanodiamonds and polymers is improved through surface chemical bonding, forming porous with good mechanical properties and stable wettability. film.
It realizes the high tensile strength, puncture strength and thermal stability of the lithium battery separator, while ensuring good wetting of the electrolyte, extending the service life of the lithium battery and improving the battery life.
Smart Images

Figure CN116180324B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a porous film material and a preparation method thereof, belonging to the technical field of film materials. Background Art
[0002] At present, the development of new energy vehicles in various countries around the world is changing with each passing day. In my country, new energy vehicles are being vigorously promoted and popularized in the lives of ordinary people, and there is a trend of replacing fuel vehicles. However, many people are still stopped by their concerns about the service life, endurance and safety of lithium batteries in new energy vehicles. The service life and endurance of lithium batteries are closely related to the materials and various performance indicators of lithium batteries. If you want to improve the service life and endurance of lithium batteries, you need to use highly sophisticated components, and such components often need to be imported and have high costs, such as the battery separator used to isolate the positive and negative electrodes of lithium battery electrolytes and ensure the passage of lithium ions.
[0003] Battery separators must have electronic insulation, a certain pore size and porosity, resistance to electrolyte corrosion, chemical and electrochemical stability, good wettability, good mechanical properties, good dimensional stability and flatness, thermal stability and good automatic shutdown protection. The current mainstream battery separators are single-layer PP and PE, and there are also double-layer PP / PE composite separators or PP / PE / PP three-layer composite separators. There are also composite battery separators with surface coating or soaking ceramic coatings and organic / inorganic composite separators. During the charging and discharging process of lithium batteries, lithium dendrites will inevitably be produced. Lithium dendrites are very sharp and can easily touch the separator during movement. Once the separator ruptures, it will cause the positive and negative electrodes to contact and the battery to short-circuit, which poses a greater safety hazard. Therefore, the mechanical strength of the separator is a prerequisite for the safety of lithium batteries. To solve this problem, existing diaphragms often increase the thickness of the diaphragm or use a composite diaphragm. Increasing the thickness of the diaphragm will cause the path for ions to pass through the diaphragm to become longer, and composite diaphragms will often cause the porosity of the diaphragm to become smaller and unevenly distributed. The thinner the diaphragm and the higher the porosity, the smaller the internal resistance of the battery and the better the high-rate discharge performance. Therefore, these methods will lead to poor ion permeability, thereby causing poor battery charging and discharging performance and endurance.
[0004] Another major factor affecting the permeability of the diaphragm to lithium ions is the wettability of the diaphragm to the electrolyte. The better the wettability, the better the permeability of lithium ions, and the better the hydrophilicity of the diaphragm, the better its wettability. The method of improving the wettability of the diaphragm in the prior art generally adopts the surface modification by coating a layer of substance on the surface of the diaphragm, but the bonding force between the surface coating material and the diaphragm is weak, and it will slowly fall off with the increase of time, and the surface coating material will cause the surface roughness of the diaphragm to increase.
[0005] Therefore, there is an urgent need to develop a porous film material with good mechanical properties, good wettability to electrolyte and high porosity, so as to solve the problem that the current lithium battery separator cannot simultaneously meet the requirements of good mechanical properties, good wettability to electrolyte and high porosity. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a porous film material, which can solve the problems of poor mechanical properties, poor wettability to electrolyte and low porosity of the porous film materials currently used as lithium battery separators.
[0007] Another object of the present invention is to provide a porous film material.
[0008] In order to achieve the above objectives, the technical solution adopted by the method for preparing the porous film material of the present invention is:
[0009] A method for preparing a porous film material comprises the following steps: electrospinning an electrostatic spinning solution to obtain a porous film material; the electrospinning solution mainly comprises a hydrophilic polymer, a functionalized nanodiamond and water, the functionalized nanodiamond comprises a nanodiamond and a hydrophilic group and a polymer group chemically bonded to the nanodiamond, the hydrophilic group is selected from ★ -COOH, ★ -OH, ★ -NH2 or any combination thereof; the structural formula of the polymer group is as shown in Formula 1; the porous film material has a porous structure;
[0010]
[0011] In Formula 1, R1, R2, and R3 are each independently selected from hydrogen, methyl, ethyl, n-propyl, or isopropyl; m is an integer greater than 0; n is an integer greater than or equal to 0; ★ represent ★ -COOH, ★ -OH, ★ -NH2, a chemical bonding point between the polymer group as shown in Formula 1 and the nano-diamond.
[0012] The preparation method of the porous film material of the present invention is simple to operate. The functionalized nanodiamond with linear polymer chain segments chemically bonded on the surface can improve the binding force between the nanodiamond and the hydrophilic polymer in the prepared porous film material, avoid the nanodiamond in the prepared porous film material from falling off, and then give full play to the good performance of the diamond's superhardness, corrosion resistance, high thermal conductivity, and electrical insulation for a long time; since the hydrophilic polymer and the functionalized nanodiamond both contain hydrophilic groups, the prepared porous film material can be guaranteed to have good hydrophilicity, which helps to improve the wettability of the porous film material to the electrolyte, and compared with the later surface hydrophilic modification treatment, the hydrophilic polymer and the functionalized nanodiamond are selected to make the hydrophilicity of the prepared porous film material more stable and uniform; the functionalized nanodiamond helps to improve the void size and porosity of the prepared porous film material. The porous film material prepared by the present invention can be used as a battery separator or a filter material.
[0013] Preferably, R1, R2 and R3 are all hydrogen.
[0014] Preferably, the functionalized nanodiamond is prepared by a method comprising the following steps: subjecting carboxylated diamond particles to an acylation reaction with a polymer as shown in Formula 2;
[0015]
[0016] In Formula 2, R1, R2, and R3 are independently selected from hydrogen, methyl, ethyl, n-propyl, or isopropyl, and x=m+n. The polymer shown in Formula 2 is a weakly alkaline linear polymer, which contains a tertiary amine functional group on its molecular chain and has ion exchange, complexation behavior, catalytic activity, and heat resistance. The -COOH group in the carboxylated nanodiamond particles undergoes an acylation reaction with the hydrogen on the third carbon atom of the imidazole group in the polymer shown in Formula 2, so that the carboxylated nanodiamond is connected to the polyvinyl imidazole molecular chain to form a chemical bond. The binding force of the chemical bond is much greater than the intermolecular attraction, so the problem of weak binding force and easy detachment in the composite film formation of inorganic materials and polymer materials is solved.
[0017] It can be understood that the acylation reaction refers to the acylation reaction between the carboxyl group in the carboxylated diamond particles and the hydrogen connected to the third carbon atom of the imidazole group in the polyvinyl imidazole, so that the carboxylated diamond particles are connected to the polyvinyl imidazole molecular chain through chemical bonds. The binding force of the chemical bond is much greater than the intermolecular attraction, thus solving the problem of weak binding force and easy detachment in the composite film formation of inorganic materials and polymer materials.
[0018] Preferably, the weight average molecular weight of the polymer as shown in Formula 2 is 20000 to 50000. For example, the weight average molecular weight of the polymer as shown in Formula 2 is 30000.
[0019] Preferably, the acylation reaction method comprises the following steps: subjecting the carboxylated diamond particles and the polymer shown in Formula 2 to the acylation reaction at 40 to 70° C. under the catalysis of H 2 SO 4 . The acylation reaction process is shown in Formula 3:
[0020]
[0021]
[0022] In formula 3, represents carboxylated diamond particles, x=m+n.
[0023] Preferably, the mass ratio of the carboxylated diamond particles to the polymer as shown in Formula 2 is (0.01-0.2):(0.5-2). For example, the mass ratio of the carboxylated diamond particles to the polymer as shown in Formula 2 is 0.1:1.
[0024] Preferably, the mass ratio of the carboxylated diamond particles to H2SO4 is (0.01-0.2):(1.96-7.84). For example, the mass ratio of the carboxylated diamond particles to H2SO4 is 0.1:4.9.
[0025] Preferably, the H2SO4 is added in the form of concentrated sulfuric acid. Preferably, the mass fraction of the concentrated sulfuric acid is 70% to 98%.
[0026] Preferably, the acylation reaction time is 3 to 8 hours.
[0027] Preferably, the polymer shown in Formula 2 is polyvinyl imidazole.
[0028] Preferably, the particle size of the carboxylated diamond particles is 10 to 30 nm.
[0029] Preferably, the carboxylated diamond particles are prepared by a method comprising the following steps:
[0030] (1) mixing diamond particles, ferrous sulfate and hydrogen peroxide in water for reaction, solid-liquid separation, washing and drying to obtain product A; the particle size of the diamond particles is 10 to 30 nm;
[0031] (2) Mix product A, dilute hydrochloric acid and hydrogen peroxide for reaction, separate solid and liquid, wash and dry to obtain carboxylated diamond particles. Nano-scale diamond particles have the characteristics of diamond, such as superhardness, corrosion resistance, high thermal conductivity and electrical insulation, and also have the characteristics of nano-materials, such as high specific surface area, a large number of dangling bonds on the surface, high chemical activity, and the smaller the grain, the higher the chemical activity. Carboxylation treatment improves its dispersibility in water on the one hand, and further improves its surface reaction activity on the other hand.
[0032] In the method for preparing carboxylated diamond particles, the function of step (1) is to generate carboxyl groups on the surface of the diamond particles, and the function of step (2) is to purify and remove impurities and iron elements.
[0033] Preferably, in step (1), the mass ratio of the diamond particles, ferrous sulfate and hydrogen peroxide is (15-25):(0.5-2):(0.9-10).
[0034] Preferably, in step (1), the mass ratio of the diamond particles to water is (15-25):(80-134).
[0035] Preferably, in step (1), the hydrogen peroxide is used in the form of hydrogen peroxide. Preferably, in step (1), the hydrogen peroxide is added in a dropwise manner. Preferably, in step (1), the dripping speed is 0.01 to 0.3 mL / min. For example, in step (1), the dripping speed is 0.1 mL / min. Preferably, in step (1), the hydrogen peroxide is 20% to 80% of the mass of the diamond particles. Preferably, in step (1), the mass fraction of the hydrogen peroxide is 30% to 50%.
[0036] Preferably, in step (1), the mixing reaction time is 2 to 8 hours.
[0037] Preferably, in step (2), the mass of dilute hydrochloric acid used per 1 g of product A is 0.01 to 0.5 g in terms of hydrogen chloride.
[0038] Preferably, in step (2), the mass of hydrogen peroxide used per 1 g of product A is 0.01 to 1 g in terms of hydrogen peroxide.
[0039] Preferably, in step (2), the hydrogen peroxide is added dropwise. Preferably, in step (2), the rate of the dropwise addition is 0.01 to 0.3 mL / min. For example, in step (2), the rate of the dropwise addition is 0.1 mL / min. Preferably, in step (2), the mass fraction of the hydrogen peroxide is 30% to 50%.
[0040] Preferably, in step (2), the temperature of the mixed reaction is 40 to 80° C. Preferably, in step (2), the time of the mixed reaction is 2 to 8 hours.
[0041] The structure of the prepared carboxylated diamond particles is shown in Formula 4:
[0042]
[0043] In Formula 4, ND represents diamond particles, and -COOH represents carboxyl groups on the surface of diamond particles. The number of carboxyl groups is much larger than that shown in the figure.
[0044] Preferably, the diamond particles are obtained by a method comprising the following steps: heat-treating micron-sized diamonds in a mixed atmosphere, and then crushing the heat-treated system to obtain diamond particles. Preferably, the mixed atmosphere is mainly composed of oxygen and nitrogen. Preferably, the volume ratio of oxygen to nitrogen is (1-5):1. For example, the volume ratio of oxygen to nitrogen is 1:1. Preferably, the temperature of the heat treatment is 300-500°C. Preferably, the time of the heat treatment is 0.5-4h. Preferably, the crushing is grinding. Preferably, the grinding medium used in the grinding is a ball medium. Preferably, the diameter of the ball medium is 0.01-0.1μm. Preferably, the grinding time is 0.5-5h.
[0045] Preferably, the hydrophilic group in the hydrophilic polymer is selected from one or any combination of hydroxyl, carboxyl and amino groups.
[0046] Preferably, the hydrophilic polymer is a hydroxylated polymer, and the hydroxylated polymer is a product of a functional polymer modified by hydroxylation. Preferably, the functional polymer is formed by polymerization of monomers including ethylene and tetrafluoroethylene. Preferably, the weight average molecular weight of the functional polymer is 30,000 to 100,000. The close arrangement of the molecular chains of ethylene tetrafluoroethylene copolymer is combined with the high porosity and uniform distribution of voids in the electrospinning process, and due to the functionalized nanodiamonds in the porous film material, the porous film material can be ensured to have not only high strength, but also adjustable void size and porosity. The use of a mixture with water as a solvent for electrospinning can avoid the problem of solvent volatilization polluting the air and easily causing fire when spinning under high voltage static electricity using organic solvents.
[0047] Preferably, the functional polymer is ethylene tetrafluoroethylene copolymer. Ethylene tetrafluoroethylene copolymer maintains the good corrosion resistance of polytetrafluoroethylene, and also has good heat resistance, wear resistance, radiation resistance, impact resistance, electrical insulation, low creep, high modulus and excellent mechanical properties. It is composited with polyvinyl imidazole connected with nanodiamonds to form a film, so that the prepared porous film material has very strong mechanical properties and can be made into ultra-thin porous film materials. The porous film material has the ability to adjust the pore size with temperature, which helps to improve the thermal stability and automatic shutdown protection of the diaphragm when used as a battery diaphragm. The use of functionalized nanodiamonds and hydroxyl-modified ethylene tetrafluoroethylene copolymers to make porous film materials can significantly improve the tensile strength of the porous film materials, and can prepare porous film materials with thin thickness and high tensile strength.
[0048] Preferably, the hydroxylation modification method comprises the following steps: mixing and reacting a reaction system mainly composed of a functional polymer, hydrogen peroxide and ammonia water at 40-50°C.
[0049] Preferably, the mass fraction of hydrogen peroxide used in the hydroxylation modification method is 30% to 50%. For example, the mass fraction of hydrogen peroxide used in the hydroxylation modification method is 40%. Preferably, the mass fraction of ammonia water used in the hydroxylation modification method is 10% to 30%. For example, the mass fraction of ammonia water used in the hydroxylation modification method is 25%.
[0050] Preferably, the mass ratio of the functional polymer, hydrogen peroxide and ammonia used in the hydroxylation modification method is (1-8):(1-4):(0.1-0.9). For example, the mass ratio of the functional polymer, hydrogen peroxide and ammonia used in the hydroxylation modification method is 5:2:0.5.
[0051] Preferably, the reaction system further comprises water. Preferably, the mass ratio of the functional polymer, hydrogen peroxide, ammonia water and water used in the hydroxylation modification method is (1-8):(1-4):(0.1-0.9):(90-100).
[0052] Preferably, the mixing is performed by grinding. Preferably, in the hydroxylation modification method, the grinding medium used in the grinding is a ball medium. Preferably, in the hydroxylation modification method, the diameter of the ball medium is 0.1 to 10 μm.
[0053] Preferably, the hydroxylation modification method further comprises the following steps: after the mixing reaction is completed, the system after the mixing reaction is separated into solid and liquid, and washed to obtain a hydroxylated polymer.
[0054] Preferably, the particle size of the solid particles in the electrospinning solution is not greater than 5 μm. For example, the particle size of the solid particles in the electrospinning solution is 0.1 to 5 μm.
[0055] Preferably, the electrospinning solution further comprises an aqueous dispersant. Preferably, the aqueous dispersant is selected from one or any combination of Tween, polyethylene glycol, ammonium polyacrylate, and sodium polyacrylate.
[0056] Preferably, the electrospinning solution is prepared by a method comprising the following steps:
[0057] Mixing the hydrophilic polymer and water to obtain dispersion A;
[0058] Mixing the functionalized nanodiamond, the aqueous dispersant and water to obtain a dispersion B;
[0059] Then, the dispersion A and the dispersion B are mixed to obtain the electrospinning solution. The hydrophilic polymer is mixed with the functionalized nanodiamond to prepare the electrospinning solution with water as the solvent, thereby avoiding the problem that the process parameters are difficult to control when two or more solvents are used and two or more needles are used in the electrospinning process.
[0060] Preferably, the solid content of the dispersion A is 10% to 60%.
[0061] Preferably, the solid content of the dispersion B is 10% to 20%. Preferably, the mass fraction of the aqueous dispersant in the dispersion B is 0.01% to 1%.
[0062] Preferably, the mass ratio of the dispersion A to the dispersion B is (0.8-4):1.
[0063] Preferably, the voltage used for electrospinning is 18-23KV, the receiving distance is 10-20cm, the air humidity is 20%-40%, and the temperature is 25-40°C. For example, the voltage used for electrospinning is 21KV, the receiving distance is 15cm, the air humidity is 30%, and the temperature is 35°C.
[0064] The technical solution adopted by the porous film material of the present invention is:
[0065] The porous film material is prepared by the method for preparing the porous film material as described above.
[0066] The method for preparing the porous film material of the invention is simple to operate, and the prepared porous film material has good tensile strength, puncture strength and thermal stability, and has good wettability to electrolyte.
[0067] Preferably, the density of the porous film material is 1.2 to 3.5 g / cm 3 For example, the density of the porous film material is 2.28 to 2.66 g / cm 3 .
[0068] Preferably, the pore size of the porous film material is 0.01-0.5 μm.
[0069] A porous film material prepared by the above-mentioned porous film material or the above-mentioned method for preparing the porous film material is used as a battery separator.
[0070] The porous film material of the present invention is used as a battery separator, has good tensile strength, puncture strength and thermal stability, and has good wettability to electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 is the particle size distribution diagram of the carboxylated diamond particles in Example 3;
[0072] Figure 2 It is a schematic diagram of the tensile strength of the porous film materials prepared in Example 3 and Examples 8-14 in the experimental examples;
[0073] Figure 3 It is a schematic diagram of the puncture strength of the porous film materials prepared in Example 3 and Examples 8-14 in the experimental examples;
[0074] Figure 4 A schematic diagram of the porosity of the porous film materials prepared in Example 3 and Examples 8-14 in the experimental examples;
[0075] Figure 5 It is a schematic diagram of the air permeability of the porous film materials prepared in Example 3 and Examples 8-14 in the experimental examples;
[0076] Figure 6 It is a schematic diagram of the thermal shrinkage rate of the porous film materials prepared in Example 3 and Examples 8-14 in the experimental examples;
[0077] Figure 7 It is a schematic diagram of the contact angle of the porous film materials prepared in Example 3 and Examples 8-14 in the experimental examples. DETAILED DESCRIPTION
[0078] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0079] 1. The specific embodiment of the method for preparing the porous film material of the present invention is as follows:
[0080] Example 1
[0081] The method for preparing the porous film material of this embodiment specifically comprises the following steps:
[0082] (1) Preparation of hydrophilic polymer
[0083] ① Mix ethylene tetrafluoroethylene copolymer powder, hydrogen peroxide (mass fraction 30%), ammonia water (mass fraction 10%), and deionized water in a mass ratio of 5:2:0.5:95 to obtain a mixture A; the weight average molecular weight of the ethylene tetrafluoroethylene copolymer is 30000;
[0084] ② The mixture A was wet-grinded for 2 h using a bead mill at 40° C. The grinding media used for grinding were grinding beads with a diameter of 0.1 to 10 μm. After the grinding, the grinding slurry and the grinding media were separated, and the grinding slurry was named mixture B;
[0085] ③ The mixture B is washed with deionized water under ultrasonic and stirring conditions, and dehydrated using a centrifuge, repeatedly until the pH of the dehydrated liquid is 7, to obtain a hydrophilic polymer with a particle size of 0.1 to 5 μm and containing a certain amount of water.
[0086] (2) Preparation of functionalized nanodiamonds
[0087] ① Place the micron-sized diamond prepared by the detonation method in a muffle furnace, then introduce a mixed atmosphere consisting of oxygen and nitrogen in a volume ratio of 1:1 into the muffle furnace to replace the air therein, and then heat the diamond to 300°C and burn for 0.5h;
[0088] ② Mix the calcined diamond with an appropriate amount of water to obtain a dispersion with a solid content of 5%, and then put the dispersion into a bead mill for wet grinding for 0.5 hours. The grinding medium used for grinding is grinding beads with a diameter of 0.01 to 0.1 μm. After the grinding is completed, the grinding slurry and the grinding medium are separated, and the grinding slurry is then solid-liquid separated and dried to obtain diamond particles. The particle size of the diamond particles is 10 to 30 nm.
[0089] ③ Diamond particles, ferrous sulfate and deionized water in a mass ratio of 20:1:100 were placed in a glass reactor and mixed evenly. Then, hydrogen peroxide (mass fraction: 30%) with a mass of 20% of the mass of the diamond particles was added dropwise to the glass reactor at a rate of 0.1 mL / min under stirring. After the addition was completed, stirring and reacting was continued for 2 h. Then, the system after stirring and reacting was filtered, and the solid obtained by filtration was washed 3 times with deionized water and dried to obtain product A.
[0090] ④ Product A and 10% dilute hydrochloric acid are placed in a glass reactor and mixed evenly. Then, the materials in the glass reactor are heated to 40° C. under stirring conditions. Hydrogen peroxide (30% by mass) is then added dropwise to the glass reactor at a rate of 0.1 mL / min. After the addition is completed, the stirring reaction is continued for 2 hours. Then, the stirred reaction system is washed with deionized water under ultrasonic and stirring conditions, and dehydrated using a centrifuge, repeatedly until the pH of the dehydrated liquid is 7. After drying, carboxylated diamond particles are obtained. The particle size of the carboxylated diamond particles is 10 to 30 nm. The mass of the dilute hydrochloric acid used for each 1 g of product A is 0.01 g in terms of hydrogen chloride, and the mass of the hydrogen peroxide used for each 1 g of product A is 0.01 g in terms of hydrogen peroxide;
[0091] ⑤ Put polyvinyl imidazole (weight average molecular weight of 30,000) in a mass ratio of 1:0.1:5, carboxylated diamond particles and concentrated sulfuric acid with a mass fraction of 98% into a glass reactor, mix them evenly, and then heat the materials in the glass reactor to 40°C under stirring conditions, keep the reaction warm for 3 hours, then cool the system after the reaction to room temperature, and then perform solid-liquid separation, and then wash the solid obtained by solid-liquid separation with deionized water until the pH of the washing liquid is 7, and then use a centrifuge to dehydrate the washed solid to obtain functionalized nanodiamonds containing a certain amount of water.
[0092] (3) Preparation of porous film materials
[0093] ① The mixture of the hydrophilic polymer prepared in step (1) and deionized water was intermittently ultrasonicated by an ultrasonic cell pulverizer for 0.1 h (ultrasonication once every 10 s, and the duration of each ultrasonication was 5 s) to obtain a dispersion A, which was an emulsion and had a solid content of 10%;
[0094] ② The mixture of the functionalized nanodiamond prepared in step (2), deionized water and an aqueous dispersant was intermittently ultrasonicated by an ultrasonic cell pulverizer for 0.1 h (ultrasonication once every 10 s, and the duration of each ultrasonication was 5 s) to obtain a dispersion B; the solid content of the dispersion B was 10%, the mass fraction of the aqueous dispersant in the dispersion B was 0.01%, and the aqueous dispersant was Tween;
[0095] ③ The mixture consisting of dispersion A and dispersion B was intermittently ultrasonicated by an ultrasonic cell disruptor for 0.1 h (ultrasonicated once every 10 s, and the duration of each ultrasonication was 5 s) to obtain an electrospinning dispersion (the particle size of the solid particles in the electrospinning dispersion was 0.1 to 5 μm); the mass ratio of dispersion A to dispersion B used to prepare the electrospinning dispersion was 4:1;
[0096] ④ The electrospinning dispersion is passed through an electrospinning machine to form an electrospinning film with a thickness of 16 μm. The electrospinning film is a porous film material. The voltage used for electrospinning is 21 KV, the receiving distance is 15 cm, the air humidity is 30%, and the temperature is 35 ° C. The density of the porous film material prepared in this embodiment is 2.28 g / cm 3 , the pore size distribution range is 0.01~0.2μm.
[0097] Example 2
[0098] The method for preparing the porous film material of this embodiment specifically comprises the following steps:
[0099] (1) Preparation of hydrophilic polymer
[0100] ① Mix ethylene tetrafluoroethylene copolymer powder, hydrogen peroxide (mass fraction 40%), ammonia water (mass fraction 25%), and deionized water in a mass ratio of 1:1:0.1:90 to obtain a mixture A; the weight average molecular weight of the ethylene tetrafluoroethylene copolymer is 60000;
[0101] ② The mixture A was wet-ground at 45° C. using a bead mill for 3 h. The grinding medium used for grinding was grinding beads with a diameter of 0.1 to 10 μm. After the grinding, the grinding slurry and the grinding medium were separated. The grinding slurry was named mixture B.
[0102] ③ The mixture B is washed with deionized water under ultrasonic and stirring conditions, and dehydrated using a filter press, repeatedly until the pH of the dehydrated liquid is 7, to obtain a hydrophilic polymer with a particle size of 0.1 to 5 μm and containing a certain amount of water.
[0103] (2) Preparation of functionalized nanodiamonds
[0104] ① Place the micron-sized diamond prepared by the detonation method in a tube furnace, then introduce a mixed atmosphere consisting of oxygen and nitrogen with a volume ratio of 3:1 into the tube furnace to replace the air therein, and then heat the diamond to 400°C and burn for 2 hours;
[0105] ② Mix the calcined diamond with an appropriate amount of water to obtain a dispersion with a solid content of 10%, and then put the dispersion into a bead mill for wet grinding for 2 hours. The grinding medium used for grinding is grinding beads with a diameter of 0.01 to 0.1 μm. After the grinding is completed, the grinding slurry and the grinding medium are separated, and the grinding slurry is then subjected to solid-liquid separation. After drying, diamond particles are obtained. The particle size of the diamond particles is 10 to 30 nm;
[0106] ③ Diamond particles, ferrous sulfate and deionized water in a mass ratio of 15:0.5:80 were placed in a glass reactor and mixed evenly. Then, hydrogen peroxide (mass fraction: 40%) with a mass of 50% of the mass of the diamond particles was added dropwise at a rate of 0.01 mL / min under stirring. After the addition was completed, the stirring reaction was continued for 4 hours. The system after the stirring reaction was then filtered, and the solid obtained by filtration was washed 4 times with deionized water and dried to obtain product A.
[0107] ④ Product A and 10% dilute hydrochloric acid are placed in a glass reactor and mixed evenly. Then, the materials in the glass reactor are heated to 60° C. under stirring conditions. Hydrogen peroxide (40% by mass) is then added dropwise to the glass reactor at a rate of 0.01 mL / min. After the addition is completed, the stirring reaction is continued for 5 hours. Then, the stirred reaction system is cleaned with deionized water under ultrasonic and stirring conditions, and dehydrated using a centrifuge, repeatedly until the pH of the dehydrated liquid is 7. After drying, carboxylated diamond particles are obtained. The particle size of the carboxylated diamond particles is 10 to 30 nm. The mass of the dilute hydrochloric acid used for each 1 g of product A is 0.2 g in terms of hydrogen chloride, and the mass of the hydrogen peroxide used for each 1 g of product A is 0.5 g in terms of hydrogen peroxide.
[0108] ⑤ Put polyvinyl imidazole (weight average molecular weight of 20000) with a mass ratio of 0.5:0.01:2, carboxylated diamond particles and concentrated sulfuric acid with a mass fraction of 98% into a glass reactor, mix them evenly, and then heat the materials in the glass reactor to 50°C under stirring conditions, keep the reaction warm for 6 hours, then cool the system after the reaction to room temperature, and then perform solid-liquid separation, and then wash the solid obtained by solid-liquid separation with deionized water until the pH of the washing liquid is 7, and then use a filter press to dehydrate the washed solid to obtain functionalized nanodiamonds containing a certain amount of water.
[0109] (3) Preparation of porous film materials
[0110] ① The mixture of the hydrophilic polymer prepared in step (1) and deionized water was sonicated by an ultrasonic cell pulverizer for 1 h (sonication once every 10 s, and the duration of each sonication was 5 s) to obtain a dispersion A, which was an emulsion and had a solid content of 40%;
[0111] ② The mixture of the functionalized nanodiamond prepared in step (2), deionized water and an aqueous dispersant is sonicated for 2 h by an ultrasonic cell crusher (sonicated once every 10 s, and the time for each ultrasonication is 5 s) to obtain a dispersion B; the solid content of the dispersion B is 15%, the mass fraction of the aqueous dispersant in the dispersion B is 0.5%, and the aqueous dispersant is polyethylene glycol;
[0112] ③ The mixture consisting of dispersion A and dispersion B was ultrasonically treated by an ultrasonic cell crusher for 1 h (ultrasonication once every 10 s, and the duration of each ultrasonication was 5 s) to obtain an electrospinning dispersion (the particle size of the solid particles in the electrospinning dispersion was 0.1 to 5 μm); the mass ratio of dispersion A and dispersion B used to prepare the electrospinning dispersion was 3:1;
[0113] ④ The electrospinning dispersion is passed through an electrospinning machine to form an electrospinning film with a thickness of 16 μm. The electrospinning film is a porous film material. The voltage used for electrospinning is 18KV, the receiving distance is 10 cm, the air humidity is 20%, and the temperature is 25°C. The density of the porous film material prepared in this embodiment is 2.35 g / cm 3 , the pore size distribution range is 0.01~0.3μm.
[0114] Example 3
[0115] The method for preparing the porous film material of this embodiment specifically comprises the following steps:
[0116] (1) Preparation of hydrophilic polymer
[0117] ① Mix ethylene tetrafluoroethylene copolymer powder, hydrogen peroxide (mass fraction 50%), ammonia water (mass fraction 30%), and deionized water in a mass ratio of 8:4:0.9:100 to obtain a mixture A; the weight average molecular weight of the ethylene tetrafluoroethylene copolymer is 100000;
[0118] ② The mixture A was wet-grinded at 50° C. using a bead mill for 5 h. The grinding media used for grinding were grinding beads with a diameter of 0.1 to 10 μm. After the grinding, the grinding slurry and the grinding media were separated. The grinding slurry was named mixture B.
[0119] ③ The mixture B is washed with deionized water under ultrasonic and stirring conditions, and dehydrated using a centrifuge, repeatedly until the pH of the dehydrated liquid is 7, to obtain a hydrophilic polymer with a particle size of 0.1 to 5 μm and containing a certain amount of water.
[0120] (2) Preparation of functionalized nanodiamonds
[0121] ① Place the micron-sized diamond prepared by the detonation method in a muffle furnace, then introduce a mixed atmosphere consisting of oxygen and nitrogen with a volume ratio of 5:1 into the muffle furnace to replace the air therein, and then heat the diamond to 500°C and burn for 4 hours;
[0122] ② Mix the calcined diamond with an appropriate amount of water to obtain a dispersion with a solid content of 20%, and then put the dispersion into a bead mill for wet grinding for 5 hours. The grinding medium used for grinding is grinding beads with a diameter of 0.01 to 0.1 μm. After the grinding is completed, the grinding slurry and the grinding medium are separated, and the grinding slurry is then solid-liquid separated and dried to obtain diamond particles. The particle size of the diamond particles is 10 to 30 nm;
[0123] ③ Diamond particles, ferrous sulfate and deionized water in a mass ratio of 25:2:120 were placed in a glass reactor and mixed evenly. Then, hydrogen peroxide (mass fraction: 50%) with a mass of 80% of the mass of the diamond particles was added dropwise at a rate of 0.3 mL / min under stirring. After the addition was completed, the stirring reaction was continued for 8 hours. The system after the stirring reaction was then filtered, and the solid obtained by filtration was washed 5 times with deionized water and dried to obtain product A.
[0124] ④ Product A and 10% dilute hydrochloric acid by mass are placed in a glass reactor and mixed evenly. Then, the materials in the glass reactor are heated to 80°C under stirring conditions. Hydrogen peroxide (mass fraction is 50%) is then added dropwise to the glass reactor at a rate of 0.3 mL / min. After the addition is completed, the stirring reaction is continued for 8 hours. Then, the stirred reaction system is cleaned with deionized water under ultrasonic and stirring conditions, and dehydrated using a centrifuge. This is repeated several times until the pH of the dehydrated liquid is 7. After drying, carboxylated diamond particles are obtained. The particle size of the carboxylated diamond particles is 10 to 30 nm. The particle size distribution of the carboxylated diamond particles is shown in the figure. Figure 1 As shown; the mass of dilute hydrochloric acid used for every 1g of product A is 0.5g in terms of hydrogen chloride, and the mass of hydrogen peroxide used for every 1g of product A is 1g in terms of hydrogen peroxide;
[0125] ⑤ Put polyvinyl imidazole (weight average molecular weight of 50,000) in a mass ratio of 2:0.2:8, carboxylated diamond particles and concentrated sulfuric acid with a mass fraction of 98% into a glass reactor and mix them evenly. Then, under stirring conditions, heat the materials in the glass reactor to 70°C and keep the reaction warm for 8 hours. Then, cool the system after the reaction to room temperature, perform solid-liquid separation, and then wash the solid obtained by the solid-liquid separation with deionized water until the pH of the washing liquid is 7. Then, use a filter press to dehydrate the washed solid to obtain functionalized nanodiamonds containing a certain amount of water.
[0126] (3) Preparation of porous film materials
[0127] ① The mixture of the hydrophilic polymer prepared in step (1) and deionized water was sonicated for 3 h by an ultrasonic cell crusher (sonicated once every 10 s, and the duration of each ultrasonication was 5 s) to obtain a dispersion A, which was an emulsion and had a solid content of 60%;
[0128] ② The mixture consisting of the functionalized nanodiamond prepared in step (2), deionized water and an aqueous dispersant is ultrasonically treated by an ultrasonic cell pulverizer for 3 h (ultrasonication once every 10 s, and the time for each ultrasonication is 5 s) to obtain a dispersion B; the solid content of the dispersion B is 20%, the mass fraction of the aqueous dispersant in the dispersion B is 1%, and the aqueous dispersant is ammonium polyacrylate;
[0129] ③ The mixture consisting of dispersion A and dispersion B was ultrasonically treated by an ultrasonic cell crusher for 3 h (ultrasonication once every 10 s, and the duration of each ultrasonication was 5 s) to obtain an electrospinning dispersion (the particle size of the solid particles in the electrospinning dispersion was 0.1 to 5 μm); the mass ratio of dispersion A to dispersion B used to prepare the electrospinning dispersion was 2.2:1;
[0130] ④ The electrospinning dispersion is passed through an electrospinning machine to form an electrospinning film with a thickness of 16 μm. The electrospinning film is a porous film material. The voltage used for electrospinning is 23 KV, the receiving distance is 20 cm, the air humidity is 40%, and the temperature is 40°C. The density of the porous film material prepared in this embodiment is 2.53 g / cm 3 , the pore size distribution range is 0.01~0.5μm.
[0131] Example 4
[0132] The difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 3 is that the mass ratio of the dispersion A and the dispersion B used to prepare the electrospinning dispersion in step (3) of the method for preparing the porous film material of this embodiment is 1.7:1. The density of the porous film material prepared in this embodiment is 2.56 g / cm 3 , the pore size distribution range is 0.01~0.5μm.
[0133] Example 5
[0134] The difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 2 is that the mass ratio of the dispersion A and the dispersion B used to prepare the electrospinning dispersion in step (3) of the method for preparing the porous film material of this embodiment is 1.3:1. The density of the porous film material prepared in this embodiment is 2.59 g / cm 3 , the pore size distribution range is 0.01~0.5μm.
[0135] Example 6
[0136] The difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 1 is that the mass ratio of the dispersion A and the dispersion B used to prepare the electrospinning dispersion in step (3) of the method for preparing the porous film material of this embodiment is 1:1. The density of the porous film material prepared in this embodiment is 2.63 g / cm 3 , the pore size distribution range is 0.01~0.5μm.
[0137] Example 7
[0138] The difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 1 is that the mass ratio of the dispersion A and the dispersion B used to prepare the electrospinning dispersion in step (3) of the method for preparing the porous film material of this embodiment is 0.8:1. The density of the porous film material prepared in this embodiment is 2.66 g / cm 3 , the pore size distribution range is 0.01~0.5μm.
[0139] Example 8
[0140] The only difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 3 is that the thickness of the electrospun film in step (3) of the method for preparing the porous film material of this embodiment is 10 μm.
[0141] Example 9
[0142] The only difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 3 is that the thickness of the electrospun film in step (3) of the method for preparing the porous film material of this embodiment is 12 μm.
[0143] Example 10
[0144] The only difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 3 is that the thickness of the electrospun film in step (3) of the method for preparing the porous film material of this embodiment is 14 μm.
[0145] Embodiment 11
[0146] The only difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 3 is that the thickness of the electrospun film in step (3) of the method for preparing the porous film material of this embodiment is 18 μm.
[0147] Example 12
[0148] The only difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 3 is that the thickness of the electrospun film in step (3) of the method for preparing the porous film material of this embodiment is 20 μm.
[0149] Example 13
[0150] The only difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 3 is that the thickness of the electrospun film in step (3) of the method for preparing the porous film material of this embodiment is 25 μm.
[0151] Embodiment 14
[0152] The only difference between the method for preparing the porous film material of this embodiment and the method for preparing the porous film material of Example 3 is that the thickness of the electrospun film in step (3) of the method for preparing the porous film material of this embodiment is 30 μm.
[0153] Comparative Example
[0154] The preparation method of the porous film material of this comparative example comprises the following steps:
[0155] (1) The mixture of the hydrophilic polymer prepared in step (1) of Example 3 and deionized water was sonicated for 3 h by an ultrasonic cell pulverizer (sonication once every 10 s, and the duration of each ultrasonication was 5 s) to obtain a dispersion A, which was an emulsion and had a solid content of 60%;
[0156] (2) treating the mixture of the carboxylated diamond particles prepared in step (2) of Example 3, deionized water and an aqueous dispersant by ultrasonication for 3 h (ultrasonication once every 10 s, and the duration of each ultrasonication is 5 s) by an ultrasonic cell pulverizer to obtain a dispersion B; the solid content of the dispersion B is 20%, the mass fraction of the aqueous dispersant in the dispersion B is 1%, and the aqueous dispersant is ammonium polyacrylate;
[0157] (3) The mixture consisting of dispersion A and dispersion B was sonicated for 3 h by an ultrasonic cell disruptor (sonication once every 10 s, and the duration of each ultrasonication was 5 s) to obtain an electrospinning dispersion (the particle size of the solid particles in the electrospinning dispersion was 0.1 to 5 μm); the mass ratio of dispersion A to dispersion B used to prepare the electrospinning dispersion was 2.2:1;
[0158] (4) The electrospinning dispersion is passed through an electrospinning machine to form an electrospinning film with a thickness of 16 μm. The electrospinning film is a porous film material. The voltage used in electrospinning is 23 KV, the receiving distance is 20 cm, the air humidity is 40%, and the temperature is 40° C.
[0159] 2. Specific embodiments of the porous film material of the present invention are as follows:
[0160] The porous film material of this embodiment is prepared by any method for preparing the porous film material in Embodiments 1-14, which will not be described in detail here.
[0161] Experimental example
[0162] In order to evaluate the mechanical properties, air permeability, heat shrinkage and wettability of the porous film materials prepared in Examples 1-7 and Comparative Examples, the tensile strength, puncture strength, porosity, air permeability, heat shrinkage when kept at 200°C for 2h and contact angle of the electrolyte on the porous film materials prepared in Examples 1-7 and Comparative Examples were tested respectively; wherein, the test method of tensile strength was carried out in accordance with the provisions of standard GB / T1040.3-2006, and the stretching direction was consistent with the spinning direction when the tensile strength was tested; the test methods of puncture strength, porosity and air permeability were carried out in accordance with the provisions of standard GB / T36363-2018 "Polyolefin Separator for Lithium Ion Batteries". The heat shrinkage when kept at 200°C for 2h refers to the heat shrinkage of the porous film material in the spinning direction when heated at 200°C for 2h, and the calculation method is in accordance with the provisions of standard GB / T36363-2018 "Polyolefin Separator for Lithium Ion Batteries".
[0163] The test results of tensile strength, puncture strength, porosity, air permeability, thermal shrinkage when kept at 200°C for 2h and contact angle of electrolyte on the porous film materials prepared in Examples 1-7 and Comparative Examples are shown in Table 1.
[0164] Table 1 Tensile strength, puncture strength, porosity, air permeability, thermal shrinkage at 200°C for 2h and contact angle of electrolyte on porous film materials prepared in Examples 1-7 and Comparative Examples
[0165]
[0166] Note: s / 100mL means the time (in seconds) required for 100mL of gas to pass through the porous film material.
[0167] As can be seen from Table 1, from the test results of the porous film materials prepared in Examples 3-7, it can be seen that as the mass ratio of dispersion A and dispersion B used to prepare the electrospinning dispersion decreases, the tensile strength, puncture strength and air permeability of the porous film gradually decrease, the porosity gradually increases, the thermal shrinkage gradually increases, and the electrolyte contact angle also has a decreasing trend but the change is not large and is much less than 90°, indicating that the porous film material has very good wettability to the electrolyte; the tensile strength, puncture strength, porosity, air permeability and thermal shrinkage of the porous film material prepared in the comparative example are significantly lower. This is because the carboxylated diamond particles used in dispersion B are free in the electrospinning solution, and the bonding force with the hydroxylated ethylene tetrafluoroethylene copolymer during film formation is weak, the mechanical properties are poor, and there is no flexible support of polyvinyl imidazole, It is difficult to form a larger porosity and air permeability, and the thermal shrinkage is smaller. Although the wetting angle has increased, it still has good wettability to the electrolyte.
[0168] In order to study the effect of the thickness of the porous film material on the tensile strength, puncture strength, porosity, air permeability, thermal shrinkage when kept at 200°C for 2h and the contact angle of the electrolyte on the porous film material, the tensile strength, puncture strength, porosity, air permeability, thermal shrinkage when kept at 200°C for 2h and the contact angle of the electrolyte on the porous film material of Examples 8-14 were tested according to the above-mentioned test method, and then the thickness of the porous film material (the thickness of the porous film materials prepared in Examples 3 and Examples 8-14 were 16μm, 10μm, 12μm, 14μm, 18μm, 20μm, 25μm and 30μm, respectively) was used as the horizontal axis, and the test results were used as the vertical axis to draw a graph. The tensile strength of the porous film materials prepared in Examples 3 and Examples 8-14 is shown in FIG. Figure 2 As shown; Example 3, the puncture strength of the porous film material prepared in Example 8-14 is as shown Figure 3 As shown; the porosity of the porous film materials prepared in Example 3 and Example 8-14 is as shown Figure 4 As shown; the air permeability of the porous film materials prepared in Example 3 and Example 8-14 is as shown Figure 5 As shown, Figure 5 The ordinate represents the time (in seconds) required for 100 mL of gas to pass through the porous film material; the thermal shrinkage of the porous film materials prepared in Examples 3 and 8-14 when kept at 200°C for 2h is as follows Figure 6 As shown; the contact angle of the electrolyte on the porous film material prepared in Example 3 and Example 8-14 is as shown Figure 7 shown.
[0169] Depend on Figure 2-7 It can be seen that with the increase of the thickness of the porous film material, the tensile strength, puncture strength and thermal shrinkage of the porous film material gradually increase, while the porosity and air permeability gradually decrease; the tensile strength, puncture strength, porosity, air permeability and thermal shrinkage of porous film materials of different thicknesses at 200°C for 2h are much higher than the requirements of the standard GB / T36363-2018 "Polyolefin Diaphragm for Lithium Ion Batteries"; the contact angle between the electrolyte and the porous film material measured by the contact angle meter is much less than 90°, indicating that the porous film material has very good wettability to the electrolyte; it can be seen that the porous film material prepared by the present invention has excellent comprehensive performance.
Claims
1. A method for preparing a porous film material for a battery separator, characterized in that: The following steps are involved: The electrospinning solution is electrospun to obtain a porous film material; the electrospinning solution is mainly composed of a hydrophilic polymer, a functionalized nanodiamond and water, the functionalized nanodiamond comprises a nanodiamond and a hydrophilic group and a polymer group chemically bonded to the nanodiamond, and the hydrophilic group is selected from ★ -COOH, ★ -OH, ★ -NH2 or any combination thereof; the structural formula of the polymer group is as shown in Formula 1; the porous film material has a porous structure; In Formula 1, R1, R2, and R3 are each independently selected from hydrogen, methyl, ethyl, n-propyl, or isopropyl; m is an integer greater than 0; n is an integer greater than or equal to 0; ★ represent ★ -COOH, ★ -OH, ★ -NH2, a chemical bonding point between the polymer group shown in Formula 1 and the nanodiamond; The functionalized nano-diamond is prepared by a method comprising the following steps: subjecting carboxylated diamond particles and a polymer as shown in Formula 2 in a mass ratio of (0.01-0.2):(0.5-2) to an acylation reaction at 40-70° C. for 3-8 hours under the catalysis of H2SO4; the particle size of the carboxylated diamond particles is 10-30 nm; the weight average molecular weight of the polymer as shown in Formula 2 is 20000-50000; In Formula 2, R1, R2, and R3 are each independently selected from hydrogen, methyl, ethyl, n-propyl, or isopropyl, and x=m+n; The carboxylated diamond particles are prepared by a method comprising the following steps: (1) mixing diamond particles, ferrous sulfate and hydrogen peroxide in water for reaction, solid-liquid separation, washing and drying to obtain product A; the particle size of the diamond particles is 10 to 30 nm; (2) mixing the product A, dilute hydrochloric acid and hydrogen peroxide, separating the solid from the liquid, washing and drying to obtain carboxylated diamond particles; The hydrophilic polymer is a hydroxylated polymer, which is a product of a functional polymer modified by hydroxylation; the functional polymer is formed by polymerizing monomers including ethylene and tetrafluoroethylene; and the weight average molecular weight of the functional polymer is 30,000 to 100,000.
2. The method for preparing a porous film material for a battery separator according to claim 1, characterized in that: In step (1), the mass ratio of the diamond particles, ferrous sulfate and hydrogen peroxide is (15-25):(0.5-2):(0.9-10); and the mixing reaction time is 2-8 hours.
3. The method for preparing a porous film material for a battery separator according to claim 1, characterized in that: In step (2), the mass of dilute hydrochloric acid used per 1g of product A is 0.01-0.5g in terms of hydrogen chloride; the mass of hydrogen peroxide used per 1g of product A is 0.01-1g in terms of hydrogen peroxide; the temperature of the mixed reaction is 40-80°C; and the time of the mixed reaction is 2-8h.
4. The method for preparing a porous film material for a battery separator according to claim 1, characterized in that: The functional polymer is an ethylene tetrafluoroethylene copolymer; the hydroxylation modification method comprises the following steps: mixing a reaction system mainly composed of a functional polymer, hydrogen peroxide and ammonia water for reaction at 40-50° C.; the mass fraction of the hydrogen peroxide used in the hydroxylation modification method is 30%-50%; the mass fraction of the ammonia water used in the hydroxylation modification method is 10%-30%; the reaction system also includes water, and the mass ratio of the functional polymer, hydrogen peroxide, ammonia water and water used in the hydroxylation modification method is (1-8):(1-4):(0.1-0.9):(90-100).
5. The method for preparing a porous film material for a battery separator according to claim 1, characterized in that: The particle size of the solid particles in the electrospinning solution is not greater than 5 μm; the electrospinning solution also includes an aqueous dispersant; the electrospinning solution is prepared by a method comprising the following steps: The hydrophilic polymer and water are mixed to obtain a dispersion A; the solid content of the dispersion A is 10% to 60%; the functionalized nanodiamond, an aqueous dispersant and water are mixed to obtain a dispersion B; the solid content of the dispersion B is 10% to 20%; the mass fraction of the aqueous dispersant in the dispersion B is 0.01% to 1%; Then, the dispersion A and the dispersion B are mixed to obtain the electrospinning solution; the mass ratio of the dispersion A to the dispersion B is (0.8-4):
1.
6. A porous film material for battery separator prepared by the method for preparing a porous film material for battery separator according to any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method and application of functionalized nano composite membrane
CN110257944A
Nanodiamond compositions and methods of making and using thereof
US20110006218A1
